A change of blood flow during strenuous physical exercises using cycle ergometer - Yamaguchi, J; Noor Azmi, Azran Azhim; Hirao, Y; Kinouchi, Y; Yamaguchi, H; Yoshizaki, K (IEEE, 2005)
Our purpose of the study is to measure the blood flow in the carotid artery during physical exercises. We have developed the blood flow velocimeter during physical exercises by using the non-invasive Doppler ultrasound method. We used it and measured blood flow in the carotid artery in which using a cycle ergometer and had two exercise tests in this report. The protocol exercise with transient response and ramp response were conducted. As a result, maximum blood flow velocities changed largely during physical exercises. In particular the maximum blood flow velocity was decreased during physical exercise in transient response. In addition, we could also detect arrhythmia that occurred in the subject immediately after exercise. For this reason, blood flow measurement during physical exercise maybe useful for the early detection of cardiovascular disease. Recently, the physical exercises are very popular for health maintenance.